-5(1+6n)=-5

Simple and best practice solution for -5(1+6n)=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(1+6n)=-5 equation:


Simplifying
-5(1 + 6n) = -5
(1 * -5 + 6n * -5) = -5
(-5 + -30n) = -5

Add '5' to each side of the equation.
-5 + 5 + -30n = -5 + 5

Combine like terms: -5 + 5 = 0
0 + -30n = -5 + 5
-30n = -5 + 5

Combine like terms: -5 + 5 = 0
-30n = 0

Solving
-30n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Divide each side by '-30'.
n = 0.0

Simplifying
n = 0.0

See similar equations:

| 2+67+x+90=360 | | 5x-10y=100 | | 8z=8z | | c/4-17=6 | | 82+67+6+90=360 | | 10+5y-2y-6= | | -25=5(-n+1) | | 20y-10yz= | | A+b+s+s+e= | | 1nx=-1 | | 4x=.5x+5 | | 33+6+77+100=360 | | 1nx=1 | | A+b+s+s+e=sb | | 2.25=0 | | F(x)=3cos(2x)+1 | | 2x+4-8x=28 | | G(3b)=3b^2-3b | | 3x+10+z+32=180 | | 0.2x+1.9=0.9 | | 2(3d-4)+10=5d+7 | | 4x+.33=.5x+5.33 | | -r/11=36 | | 12=1/5x | | F(3)=4x+9 | | 12=3(v-2) | | X=1.45 | | F(3)=4x-9 | | 1/3(2x-5)=6 | | 3g-2h=5 | | n-1+7n=7 | | 15=-15/8v |

Equations solver categories